Rapamycin persistently improves cardiac function in aged, male and female mice, even following cessation of treatment. Issue 2 (10th December 2019) - Quarles, Ellen; Basisty, Nathan; Chiao, Ying Ann; Merrihew, Gennifer; Gu, Haiwei; Sweetwyne, Mariya T.; Fredrickson, Jeanne; Nguyen, Ngoc‐Han; Razumova, Maria; Kooiker, Kristina; Moussavi‐Harami, Farid; Regnier, Michael; et al.
Abstract: Even in healthy aging, cardiac morbidity and mortality increase with age in both mice and humans. These effects include a decline in diastolic function, left ventricular hypertrophy, metabolic substrate shifts, and alterations in the cardiac proteome. Previous work from our laboratory indicated that short‐term (10‐week) treatment with rapamycin, an mTORC1 inhibitor, improved measures of these age‐related changes. In this report, we demonstrate that the rapamycin‐dependent improvement of diastolic function is highly persistent, while decreases in both cardiac hypertrophy and passive stiffness are substantially persistent 8 weeks after cessation of an 8‐week treatment of rapamycin in both male and female 22‐ to 24‐month‐old C57BL/6NIA mice. The proteomic and metabolomic abundance changes that occur after 8 weeks of rapamycin treatment have varying persistence after 8 further weeks without the drug. However, rapamycin did lead to a persistent increase in abundance of electron transport chain (ETC) complex components, most of which belonged to Complex I. Although ETC protein abundance and Complex I activity were each differentially affected in males and females, the ratio of Complex I activity to Complex I protein abundance was equally and persistently reduced after rapamycin treatment in both sexes. Thus, rapamycin treatment in the aged mice persistently improved diastolic function and myocardial stiffness, persistently altered the cardiac proteome in the absence of persistent metabolic changes, and led to persistent alterations in mitochondrial respiratory chain activity. These observations suggest that an optimal translational regimen for rapamycin therapy that promotes enhancement of healthspan may involve intermittent short‐term treatments. Abstract : Cardiac morbidity and mortality increase with age in both mice and humans. Here, we demonstrate that 8‐week treatment with rapamycin is sufficient to persistently improve diastolic function, decrease age‐related cardiac hypertrophy and passive stiffness, and modulate the cardiac proteome, even a further 8 weeks after cessation of treatment. These observations suggest that an optimal translational regimen for rapamycin therapy that promotes enhancement of healthspan may involve intermittent short‐term treatments.